2007
DOI: 10.1016/j.yjmcc.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-like Factors (KLFs) in muscle biology

Abstract: The Kruppel-like Factor (KLF) family of zinc-finger transcription factors are critical regulators of cell differentiation, phenotypic modulation and physiologic function. An emerging body of evidence implicates an important role for these factors in cardiovascular biology, however, the role of KLFs in muscle biology is only beginning to be understood. This article reviews the published data describing the role of KLFs in cardiomyocytes, smooth muscle cells, and skeletal muscle and highlights the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 99 publications
1
65
0
2
Order By: Relevance
“…64 Recent studies revealed the important role of KLFs as regulators of cardiac biology. 65 The family of KLFs was found to control ␤-catenin-dependent transcription in several tissue compartments like the gut and the heart. Possibly, KLF proteins allow for tissue specific control of ␤-catenin transcription because KLF4 regulates transcription in the small intestine whereas we found another member of the same family, namely KLF15, to control ␤-catenin-dependent transcription in the heart.…”
Section: Nuclear Negative Interaction Partners Of ␤-Catenin Attenuatementioning
confidence: 99%
“…64 Recent studies revealed the important role of KLFs as regulators of cardiac biology. 65 The family of KLFs was found to control ␤-catenin-dependent transcription in several tissue compartments like the gut and the heart. Possibly, KLF proteins allow for tissue specific control of ␤-catenin transcription because KLF4 regulates transcription in the small intestine whereas we found another member of the same family, namely KLF15, to control ␤-catenin-dependent transcription in the heart.…”
Section: Nuclear Negative Interaction Partners Of ␤-Catenin Attenuatementioning
confidence: 99%
“…KLFs are known to play several roles in muscle cell development (46), and it has been shown that in cardiac myocytes, expression of KLF3 changes rapidly in response to stimuli leading either to hypertrophy or apoptosis (29). KLF3 has also recently been identified as a transcriptional regulator of skeletal muscle differentiation (28).…”
Section: Klf3 and Muscle Cell Biologymentioning
confidence: 99%
“…Members of the Krüppel-like factor (KLF) family of transcription factors are important regulators of development, cellular differentiation and growth, and the pathogenesis of various diseases, including cancer and cardiovascular disease (13). We previously used Klf5 +/-mice to show that KLF5 is required for cardiac hypertrophy and fibrosis in response to continuous infusion of angiotensin II (AII) (14,15).…”
Section: Introductionmentioning
confidence: 99%